Persepsi Klien dan Pihak Yang Berkepentingan Terhadap Profesionalisme Dan Kualitas Pelayanan Notaris - Aidil Huda, Andri Nurwandri, Mhd Hamdi, Selamet Mujiono, Wiranto Akbar, Beny Ridho Septiansyah Tambu (Pusdikra Publishing, 2023)
This article is a research that aims to examine how much clients perceive the professionalism of a notary, to find out the various forms of services provided by notaries to their clients. Furthermore, this research also aims to find out who the clients are who receive notary services and what the obstacles and quality of these notary services are. This research uses the literature review method, which is a study used to collect information and data with the help of various kinds of materials in libraries such as documents, books, journals, magazines, historical stories and so on. The results obtained from this research are that a notary is a profession that occupies a legal position whose job is to assist clients in issuing deeds where the deed contains clear and correct information. The obstacle faced by a notary in making a deed is usually falsification of the contents and the target of blame is the notary. Therefore, a professional notary must maintain a code of ethics in carrying out notarial services.